A Comparison of MRI Quantitative Susceptibility Mapping and TRUST-Based Measures of Brain Venous Oxygen Saturation in Sickle Cell Anaemia - Murdoch, Russell; Stotesbury, Hanne; Hales, Patrick W.; Kawadler, Jamie M.; Kölbel, Melanie; Clark, Christopher A.; Kirkham, Fenella J.; Shmueli, Karin (Frontiers in Physiology, 2022)
In recent years, interest has grown in the potential for magnetic resonance imaging (MRI) measures of venous oxygen saturation (Yv) to improve neurological risk prediction. T2-relaxation-under-spin-tagging (TRUST) is an MRI technique which has revealed changes in Yv in patients with sickle cell anemia (SCA). However, prior studies comparing Yv in patients with SCA relative to healthy controls have reported opposing results depending on whether the calibration model, developed to convert blood T2 to Yv, is based on healthy human hemoglobin (HbA), bovine hemoglobin (HbBV) or sickle hemoglobin (HbS). MRI Quantitative Susceptibility Mapping (QSM) is an alternative technique that may hold promise for estimating Yv in SCA as blood magnetic susceptibility is linearly dependent upon Yv, and no significant difference has been found between the magnetic susceptibility of HbA and HbS. Therefore, the aim of this study was to compare estimates of Yv using QSM and TRUST with five published calibration models in healthy controls and patients with SCA. 17 patients with SCA and 13 healthy controls underwent MRI. Susceptibility maps were calculated from a multi-parametric mapping acquisition and Yv was calculated from the mean susceptibility in a region of interest in the superior sagittal sinus. TRUST estimates of T2, within a similar but much smaller region, were converted to Yv using five different calibration models. Correlation and Bland-Altman analyses were performed to compare estimates of Yv between TRUST and QSM methods. For each method, t-tests were also used to explore group-wise differences between patients with SCA and healthy controls. In healthy controls, significant correlations were observed between QSM and TRUST measures of Yv, while in SCA, there were no such correlations. The magnitude and direction of group-wise differences in Yv varied with method. The TRUST-HbBV and QSM methods suggested decreased Yv in SCA relative to healthy controls, while the TRUST-HbS (p < 0.01) and TRUST-HbA models suggested increased Yv in SCA as in previous studies. Further validation of all MRI measures of Yv, relative to ground truth measures such as O15 PET and jugular vein catheterization, is required in SCA before QSM or TRUST methods can be considered for neurological risk prediction.